2019
DOI: 10.1007/s41315-019-00086-3
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve bionic interface: a review of electrodes

Abstract: As the demand for sensory feedback to and from prosthetic limbs becomes increasingly desirable, implantable neural interfaces are becoming more attractive. Here, we briefly review the current landscape of extra-neural electrodes for interfacing the peripheral nervous system exploring both clinical and exploratory sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 66 publications
0
42
0
Order By: Relevance
“…VNS Therapy, Cyberonics, USA). Most of the others are still in research or undergoing clinical trials [ 119 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…VNS Therapy, Cyberonics, USA). Most of the others are still in research or undergoing clinical trials [ 119 ].…”
Section: Main Textmentioning
confidence: 99%
“…Incorporating transistors into the electrodes directly to enable connection multiplexing is one of the ways to mitigate this problem [ 188 , 189 ]. Readers interested in neural electrode designs are suggested to consult other more in-depth reviews in this area [ 119 , 172 , 176 , 177 , 190 ].…”
Section: Main Textmentioning
confidence: 99%
“…They are fabricated with various designs and are still continuing to be developed in advanced forms [58][59][60][61][62][63][64][65][66]. These designs are named and classified according to their morphological properties [10]. We will outline the types that have been proposed since it was first coined.…”
Section: Extraneural Electrodesmentioning
confidence: 99%
“…The electrical contacts inside the tube may be concentric or longitudinal. The size of the electrode must be predetermined according to the target nerve [10], the inner diameter being slightly wider than the nerve. An interesting study conducted with pigs observed the outcomes of [50] laparoscopic implantation of split cylinder cuff electrodes on pelvic nerves for 3 months [67], where the electrodes were functional at the end of the study.…”
Section: Extraneural Electrodesmentioning
confidence: 99%
“…The consensus is that electrical neural interfaces to the PNS offer the best near-term prospect for highly capable and naturalistic sensory feedback [14], [15]. However, several major challenges were identified [16]- [18] including: the trade off between the selectivity and long term stability of electrodes; targeting of axons innervating specific areas of the body and specific receptor types; methods of modulating the neural signals to provide high quality sensation; and a low power implantable device capable of delivering the stimulation patterns to a selective electrode interface. A multipronged approach to address these challenges was pursued with a key element being the development of a chronic, smallrodent neuroscience platform to investigate and demonstrate advances [19]- [21].…”
mentioning
confidence: 99%